Dark energy and the challenges to the standard cosmological model - Alcaniz, Jailson; Von Marttens, Rodrigo; Carneiro, Saulo (Cadernos de Astronomia, 2026)
Observational evidence that the Universe is undergoing accelerated expansion represents one of the main challenges of modern cosmology, usually attributed to the presence of a dominant component known as dark energy. The standard cosmological model, ΛCDM, provides a consistent description of a wide range of observations, but faces significant difficulties from both a theoretical and observational standpoint. In this article, we present a review of the ΛCDM model, discussing its theoretical foundation and the main observational tests that support its validity. We emphasize recent observational strains, such as those associated with the Hubble constant (H0) and the amplitude of matter fluctuations (S8), as well as recent results from the DESI survey that suggest possible deviations from the standard model. We also discuss the implications of these strains and possible extensions of the model, highlighting the role of scenarios with dynamic dark energy. This overview seeks to provide an updated view of the challenges faced by contemporary cosmology and the prospects for understanding cosmic acceleration.